Stability analysis of geosynthetic-reinforced soil bridge abutments under extreme rainfall conditions - Qiangqiang HUANG; Feifan REN (Zhongguo dizhi zaihai yu fangzhi xuebao)
Geosynthetic-reinforced soil (GRS) abutments have demonstrated significant potential in road and transportation engineering due to their cost-effectiveness, ease of construction, and eco-friendly characteristics. However, the increasing frequency of extreme rainfall events in recent years has significantly impacted on the deformation and stability of these structures. This study systematically evaluated the performance of GRS abutments under traffic loads and extreme rainfall conditions through model tests and numerical analysis. The findings indicate that the numerical model developed with the DBLEAVES-X program can accurately simulates the mechanical response of GRS abutments under conditions of rainfall infiltration, confirming its reliability in the analysis of unsaturated soil mechanics. Parameter analysis reveals that rainfall intensity and the permeability coefficient of the backfill significantly influence the abutment’s resistance to rainfall. Using high-permeability backfill with a permeability coefficient of 1.0×10−2 cm/s can significantly enhance the abutment’s resistance to rainfall, maintaining stability even under extreme rainfall conditions of 200 mm/h. In contrast, a permeability coefficient of 1.0×10−3 cm/s or 1.0×10−4 cm/s may lead to rapid accumulation of pore water pressure, causing soil swelling deformation and substantially increasing the risk of deformation and instability of the abutment. Therefore, it is advisable in practical engineering design to prioritize high-permeability backfill materials, optimize drainage system designs, and implement specific protective measures to enhance the long-term stability and safety of the GRS abutments under complex environmental conditions.